Laser excitation of gigahertz vibrations in Cauliflower mosaic viruses' suspension. (31st July 2018) - Tcherniega, N V; Pershin, S M; Bunkin, A F; Donchenko, E K; Karpova, O V; Kudryavtseva, A D; Lednev, V N; Mironova, T V; Shevchenko, M A; Strokov, M A; Zemskov, K I
Abstract: The interaction of laser pulses with the Cauliflower mosaic virus (CaMV) in a Tris-HCl pH7.5 buffer is investigated. 20 ns ruby laser pulses are used for the excitation. Spectra of the light passing through the sample and reflected from it are registered with the help of a Fabri–Perot interferometer. Stimulated low-frequency Raman scattering (SLFRS) in a CaMV suspension is registered. The SLFRS frequency shift, conversion efficiency and threshold are measured for the first time, to the best of our knowledge.